2014
DOI: 10.1111/bju.12541
|View full text |Cite
|
Sign up to set email alerts
|

Do ureteric stent extraction strings affect stent‐related quality of life or complications after ureteroscopy for urolithiasis: a prospective randomised control trial

Abstract: Objective To determine whether ureteric stent extraction strings affect stent‐related quality of life (QoL) or increase complications after ureteroscopy (URS) for stone disease. Patients and Methods In all, 68 patients undergoing URS (October 2011 to May 2013) for stone disease were randomised to receive a ureteric stent with or without an extraction string. Patients completed the Ureteric Stent Symptom Questionnaire (USSQ) on postoperative days 1 and 6, and 6 weeks after stent removal. Pain was assessed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
91
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 17 publications
5
91
1
Order By: Relevance
“…Barnes and colleagues reported similar findings in their study. 15 In their prospective, randomized study, they found no difference in visual analog pain scores between patients who had stents removed by cystoscopy and those who had theirs removed by stent string.…”
Section: Discussionmentioning
confidence: 95%
“…Barnes and colleagues reported similar findings in their study. 15 In their prospective, randomized study, they found no difference in visual analog pain scores between patients who had stents removed by cystoscopy and those who had theirs removed by stent string.…”
Section: Discussionmentioning
confidence: 95%
“…A questionnaire for stent symptoms was developed [6] (addressing pain, voiding symptoms, work performance, sexual health, overall general health and additional problems) [7] and it can form the base for future analysis of our cohort. Alpha blockade is associated with decreased stent related morbidity and smaller studies have shown benefit of anticholinergic medication.…”
Section: Discussionmentioning
confidence: 99%
“…Tethered stents eliminate the need for a second procedure for removal. Studies have demonstrated that this can be done safely by the patient at home, eliminating the need for a return visit to an out‐patient clinic for removal . Despite this, many surgeons are still reserved about their utility given their associated complications.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, many surgeons are still reserved about their utility given their associated complications. Of particular concern is stent migration, which frequently results from the tether getting caught on clothing, or from accidental removal during hygiene practices, particularly in female patients . Tethered stents are more frequently used in cases where short stent‐dwell times are anticipated; although even in these instances, some surgeons will still choose to use a non‐tethered stent for fear of complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation